Indice de satisfação profissional entre enfermeiros do serviço de atendimento movel de urgência – SAMU no município de Bauru e Regionais - Lopes, Roberto de Campos (2018)
Mobile Medical Emergency Service (SAMU – Serviço de Atendimento Móvel de Urgência) was conceived in France in 1986. In Brazil, the first SAMU was deployed in the city of Campinas, through the coordinating physician José Roberto Hansen and officially inaugurated in June 1996 by the mayor José Roberto Magalhães Teixeira. However, only in 2002, the Ministry of Health invested resources to train professionals to this service, so 460 medical and nursing professionals were trained in the country for urgent and emergency care. At the end of the same year, the ordinance number 2.048 was published, which establishes the Technical Regulation for State Emergency and Emergency Systems, strengthening the concepts that were in force at SAMU in Campinas. SAMU´s nurse is a professional with, at least, bachelor science in nursing, duly registered at a regional nursing council of its jurisdiction and with skills for nursing actions in mobile prehospital care. So, it is verified the importance of this professional category among this relevant public health policies. In this way, the knowledge about these professional´s satisfaction is issue of interest, since this component is also important so that urgency and emergency care system itself can act effectively. It is proposed, therefore, to identify and contextualize the index of job satisfaction (ISP - Índice de Satisfação Profissional) of this category as a way of subsidizing health managers, policymakers and legislators so that, with this information and considerations, they can better understand the role, difficulties and needs of this category, with a view to improving this unique contribution to the health care of brazilian citizen, which is the Mobile Medical Emergency Service - SAMU. Data were analyzed by descriptive statistics, including absolute and relative frequencies, means and standard deviations. An attitudinal scale consisted of 44 assertions structured by a Likert-type scale and a scale of the Professional Satisfaction Index (ISP) part A and part B. As results, in Part A, Autonomy, Work requirements and Interaction were the most valued by the participants. In part B, in the Professional Status, presented little importance, however, satisfied with the same component. As for the Remuneration, there was low satisfaction, where the monthly income of 85% of the participants is between 3 and more than 5 minimum brazilian salaries. The group studied´s ISP result presented a value of 10.30, with variation between 7.37 and 13.11. This result allows to conclude that the group studied´s professional satisfaction is low.